Air Contamination and Ecological Information Disclosure from South Africa’s High Energy Consumption Industries - Nyahuna, Thomas; Doorasamy, Mishelle (International Journal of Environmental, Sustainability, and Social Science, 2026)
Globally, South Africa is currently amongst the countries with the poorest air pollution. Organizational ecological information disclosure has recently become a progressively more prevalent method for ecological by-laws. However, at the moment, there needs to be empirical confirmation of the organization’s ecological information disclosure effects of air contamination. This research investigates the relationship between air contamination and organization ecological information disclosure by applying cross-sectional data gathered from listed South African companies in high-energy consumption sectors from 2015 to 2021. The findings disclose that the link between air contamination and organizational ecological information disclosure is substantially adverse. The Northern Province significantly affects organizational ecological information disclosure compared to the Eastern Province. Furthermore, the effect air contamination has on organization ecological information disclosure also varies in companies situated in the provinces with various corporate ecological information disclosure transparency. This study portrays the interaction between air contamination and ecological information disclosure expansion in emerging economies such as South Africa.